Solar panel tracking control. Tracking the variations caused due to reflection from snow and other factors - Pandey, Saroj (UiT Norges arktiske universitet, 2016)
This report presents the design and simulations of a dual-axis solar tracker. This solar tracker works solely based on the output power of the PV panel mounted to it. It does not use any photosensors to orient the PV module. Describing the process in short, the position of the Sun is first calculated based on time and location information. Since this solar panel will be mounted here at UiT, Norges Arktiske Universitet, Narvik. So, it’s latitude and longitude is always fixed. Theoretically, PV panel should be placed such that it’s face is perpendicular to the Sun. But the optimal position for the PV module may be slightly different from the astronomical position (facing perpendicular to the Sun) due the reflection of snow and other factors. So to track for the optimal position, the panel is moved in the tilt direction first. And the tilt angle is increased slightly by a certain step size and the output power is compared in each tilt angles. The tilt angle that gives maximum power is set as optimal tilt angle. The PV panel is then kept at this optimal tilt angle and then the same process is repeated to find the optimal azimuth angle. For the movement of the PV panel a slewing drive has been selected by other student groups. The other half of this report deals with the control of the dc motors used in the slewing drive. The rotation of the dc motors are observed and controlled so that the PV module always faces the correct direction that is required during the tracking process. Strong wind can cause mechanical damage to the PV module. Therefore, when strong wind over the danger limit is detected, the PV panels is kept parallel to the ground to minimize the surface area that comes in contact with the strong wind. When the system starts for the first time or after a power failure then It should first put itself to the 90 ̊ tilt and 0 ̊ azimuth position. In short, this report details the complete control system for dual-axis solar tracker and the protection from strong Wind.